Acute carbohydrate restriction induces a higher weight loss and preserves the athletic performance of Brazilian jiu-jitsu athletes - Mendes-Netto, R. S.; Matos, R. C.; Maynard, D. d. C.; de Lima, L. E.; Nardelli, C.; Brito, C. J.; Grigolleto, M. E. d. S. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2023)
Background and objective. Brazilian Jiu-jitsu (BJJ) is a combat sport with intense physical contact, emphasizing takedowns, and with a time limit of 10 minutes per fight, which requires strength, flexibility, motor coordination, and good aerobic endurance. Carbohydrate restriction is a widely used strategy for weight loss, yet its application to Brazilian Jiu-Jitsu athletes remains debata- ble, especially regarding the effects on energy metabolism and performance. Material and Methods. This study assessed the acute effect of carbohydrate restriction on metabolic variables, weight loss and phys- ical fitness tests. A randomized clinical trial was composed of 16 BJJ male athletes. Participants were randomized into 2 groups according to dietary strategy: R-CHO (2-3 g/kg.d-1), n=10, and A-CHO (5-7 g/kg.d-1), n=6. Four physical fitness tests and blood markers of energy metabolism and muscle damage at baseline and follow-up were assessed. Results. The main results indicated that both diet strategies promoted weight loss and did not affect performance. Regarding energy metabolism markers, carbohydrate restriction for 28 days lead to an increase in blood lactate and creatinine after an intense exer- cise bout. In spite of increased uric acid in the R-CHO group, both interventions caused reductions in its levels. Blood glucose increased in both groups at baseline. Conclusions. In conclusion, R-CHO promoted a higher weight loss and increased the mobilization of fast energy reserves, how- ever these metabolic changes did not affect performance.